Gênero, educação e desenvolvimento: os Objetivos de Desenvolvimento do Milênio de número dois e três na América Latina - Moraes, Thaís G.A. de (Revista Punto Género, 2012)
This article aims to analyze the impact of the Millennium Development Goals (MDGs) twoand three in Latin America. Firstly, it will explore the relations between the MDGs two (achieveuniversal primary education) and three (promote gender equality and empower women).Secondly, it will present the particularities of contemporary Latin America in what relates togender equality in education. Finally, it will analyze a very common policy in the region, whichhas been considerably impacting Latin America with regards to access to primary educationand gender equity: the Conditional Cash Transfer Programs. This research paper's goal is tocontribute to the achievement of the MDGs two and three in Latin America by encouragingactions from governments, civil society and the private sector.